1998
DOI: 10.1016/s0741-5214(98)70296-4
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing: A paradigm for lumen narrowing after arterial reconstruction

Abstract: Lumen narrowing after angioplasty in this model of atherosclerosis is caused largely by decreased artery wall diameter. The pattern of matrix and integrin expression within the injured artery wall is in many ways analogous to that of healing wounds. These observations suggest that tissue contraction may play a role in lumen narrowing at sites of arterial reconstruction. Strategies to inhibit wound contraction may prove effective in preventing restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 39 publications
8
104
0
1
Order By: Relevance
“…Although data are not available on the fate of versican during the regression process in this model, it is of interest to note that immunohistochemical analysis of versican (using 2B1 against the G3 globular domain) in human arteries after balloon angioplasty showed an accumulation of versican during the first 3 months and a decrease thereafter (Imanaka-Yoshida et al 2001, Matsuura et al 1996. A similar pattern was also observed in nonhuman primate arteries after balloon angioplasty (Geary et al 1998). Like angioplasty, stent placement also initially stimulates intimal hyperplasia in animal models and human arteries.…”
Section: Versican Metabolism In Intimal Regressionsupporting
confidence: 67%
“…Although data are not available on the fate of versican during the regression process in this model, it is of interest to note that immunohistochemical analysis of versican (using 2B1 against the G3 globular domain) in human arteries after balloon angioplasty showed an accumulation of versican during the first 3 months and a decrease thereafter (Imanaka-Yoshida et al 2001, Matsuura et al 1996. A similar pattern was also observed in nonhuman primate arteries after balloon angioplasty (Geary et al 1998). Like angioplasty, stent placement also initially stimulates intimal hyperplasia in animal models and human arteries.…”
Section: Versican Metabolism In Intimal Regressionsupporting
confidence: 67%
“…31 However, numerous vascular diseases are characterized by the accumulation of smooth muscle cells in the intimal layer of blood vessels where they are surrounded by newly synthesized extracellular Wnt3a alters smooth muscle cell phenotype JM Carthy et al matrix. 3,4,32 These cells are generally thought of as dedifferentiated and synthetic, in that they display a loss of contractile differentiation, but an increased capacity to synthesize matrix proteins. 31 Although traditionally it has been thought that smooth muscle cells existed in either a synthetic or contractile state, it is now being recognized that there is considerable heterogeneity in smooth muscle cell populations and in some instances, contractile differentiation markers may be expressed simultaneously with matrix synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Geary et al 48 demonstrated that the spatial temporal pattern of events after angioplasty, including deposition of extracellular matrix, is quite analogous to healing wounds and culminates in luminal narrowing. In addition to the physical wounds caused by angioplasty, plaque fractures and plaque ruptures can also be viewed as "wounds," which may eventually result in luminal narrowing as a result of normal prolonged wound healing.…”
Section: Discussionmentioning
confidence: 99%